Discourse in Música Latinoamericana Cultural Projects from Nueva Canción to Colombian Canción Social - Katz-Rosene, Joshua (2021)
In this article, I follow the discourses elaborated around música latinoamericana («Latin American music»), a broad musical category encompassing a wide range of Latin American —but especially Andean— folk genres within successive, interrelated «cultural projects». I examine the extra-musical meanings attributed to this stylistic mode in the nueva canción (new song) movements of protest music in the Southern Cone, the transnational nueva canción latinoamericana (Latin American New Song) network to which they gave rise, and ultimately focus on música latinoamericana’s development in Colombia. During the mid 1970s, the initial Colombian practitioners of música latinoamericana adopted several facets of the discourse pertaining to this music —along with the musical models themselves— from nueva canción latinoamericana. However, they later reined claims about the style’s significance, its distinctiveness from other musical genres, and its political symbolism to fit changing cultural contexts in the cities of the Colombian interior. I argue that the discursive «work» undertaken in these cultural projects has ensured that música latinoamericana continues to be equated with antiestablishment politics in Colombia, and hence that it remains closely tied to canción social («social song»), the present-day category for socially conscious music.